Interleukin-23 receptor expressing γδ T cells locally promote early atherosclerotic lesion formation and plaque necrosis in mice. Issue 14 (13th December 2021) - Gil-Pulido, Jesus; Amézaga, Núria; Jorgacevic, Ivana; Manthey, Helga D; Rösch, Melanie; Brand, Theresa; Cidlinsky, Peter; Schäfer, Sarah; Beilhack, Andreas; Saliba, Antoine-Emmanuel; Lorenz, Kristina; Boon, Louis; et al.
Abstract: Aims: Atherosclerosis is a chronic inflammatory disease of the vessel wall controlled by local and systemic immune responses. The role of interleukin-23 receptor (IL-23R), expressed in adaptive immune cells (mainly T-helper 17 cells) and γδ T cells, in atherosclerosis is only incompletely understood. Here, we investigated the vascular cell types expressing IL-23R and addressed the function of IL-23R and γδ T cells in atherosclerosis. Methods and results: IL-23R + cells were frequently found in the aortic root in contrast to the aorta in low-density lipoprotein receptor deficient IL-23R reporter mice ( Ldlr −/− Il23r gfp/+ ), and mostly identified as γδ T cells that express IL-17 and GM-CSF. scRNA-seq confirmed γδ T cells as the main cell type expressing Il23r and Il17a in the aorta. Ldlr − / − Il23r gfp/gfp mice deficient in IL-23R showed a loss of IL-23R + cells in the vasculature, and had reduced atherosclerotic lesion formation in the aortic root compared to Ldlr −/− controls after 6 weeks of high-fat diet feeding. In contrast, Ldlr −/− Tcrδ −/− mice lacking all γδ T cells displayed unaltered early atherosclerotic lesion formation compared to Ldlr − / − mice. In both HFD-fed Ldlr −/− Il23r gfp/gfp and Ldlr −/− Tcrδ −/− mice a reduction in the plaque necrotic core area was noted as well as an expansion of splenic regulatory T cells. In vitro, exposure of bone marrow-derived macrophages to both IL-17A and GM-CSF induced cell necrosis, and necroptotic RIP3K and MLKL expression, as well as inflammatory mediators. Conclusions: IL-23R + γδ T cells are predominantly found in the aortic root rather than the aorta and promote early atherosclerotic lesion formation, plaque necrosis, and inflammation at this site. Targeting IL-23R may thus be explored as a therapeutic approach to mitigate atherosclerotic lesion development. Graphical Abstract: